Exploring algal blooms for biofuel production and its environmental trade-offs - Sonekar, Dr. Ratna; Tandan, Dr. Abhinesh Kumar (International Journal of Aquatic Research and Environmental Studies, 2025)
The algal blooms have recently been a promising biological resource for producing sustainable biofuels due to their high growth rates, high lipid content, and ability to grow in other water bodies. In this paper, the two aspects of algae blooms will be explained as the source of renewable energy and a cause of severe ecological issues. Even though artificial/controlled algae growth can be incorporated in alleviating carbon and the consumption of fossil fuels, uncontrolled algae growth, especially the harmful algae blooms (HABs), can be detrimental to the quality of water, the ecological balance of the water bodies, and may cause and contribute to morbidity and mortality of both humans and organisms. The following paper will provide a comparison of the environmental trade-offs of using algal blooms to create biofuel on the basis of nutrient availability, carbon sequestration, environmental impact, and lifecycle sustainability. That is why it is essential to understand such trade-offs to develop responsible biofuels strategies that can balance energy needs and environmental safety.
Keywords: Algal blooms, Biofuel production, Environmental trade-offs, Harmful algal blooms (HABs), Sustainability, Renewable energy, Ecosystem impacts, Lipid content, Carbon capture